Pengembangan Sistem Informasi Penjualan Berbasis Web Menggunakan Metode Prototyping Pada Toko Bay Sticker - Nanang Tedi Kurniadi (Jurnal SIGMA, 2020)
The Bay Sticker shop is engaged in the cutting sticker business in its sales depending on regular consumers and consumers in the area around the shop, recording reports is still manual so that data search difficulties and data loss often occur and because the Bay Sticker Shop is related to graphic design, the delivery of information often occurs. The purpose of this research is to produce a new sales system at the Bay Sticker Shop by using a web-based application using the prototyping method and the application program design modeling using UML (Unified Modeling Language), and using PHP as a programming language and MySQL as a database. This research produces a sales information system that is fully managed by an administrator in controlling all information related to product data management, consumer data, sales report data, and a special menu for consumers to obtain information and be able to make online purchase transactions. Keywords : Bay Sticker Shop, Website, Prototyping, UML, PHP, MySQL.